Respuesta :
Answer:
the oldest sibling is 12 years old.
The middle child is 9 years old.
The youngest child is 6 years old.
Step-by-step explanation:
Let the age of the youngest child be x
Then the oldest child will be 2x.
The middle child will be x + 3.
Since the combined age is 27;
x + 2x + x + 3 = 27
4x = 27 - 3
x = 24 / 4
x = 6
now 2x = 12 and x + 3 = 9
Answer:
oldest is 12
middle is 9
youngest is 6
all add up to 27
Step-by-step explanation
idk if i did this right but i did 27 -3 =24
then i divide 24 by 2 which is twelve (the oldest's age)
then 12 divided by 2 is 6 which is the age of the youngest one
6 + 3 is 9, which is the age of the middle one.